Women participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of women participating in the 1986 y-Walk. They are walking on Almaden Boulevard and are probably crossing West San Fernando Street in a crosswalk. Some of the people are wearing tee shirts that read: "Walk for women. YWCA 1986" and some are carrying balloons. The tall white building in the background is the Hotel DeAnza.